2019
DOI: 10.1292/jvms.18-0485
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of genetic contribution to patellar luxation in Toy Poodle puppies

Abstract: Patellar luxation (PL) is one of the most common orthopedic disorders in dogs and a genetic factor is considered to play an important role in the development of PL. Genomic analysis has attempted to identify the genetic markers associated with the development of PL but only suggestive markers have been identified. Carefully selecting breeds with higher incidence rates of congenital PL as well as affected dogs with more severe symptoms are required, but such information remains limited to date. This study aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…These factors have the potential to cause instability independently, though the possibility of an interplay between the two exists, as seen with other polygenic, multifactorial traits in dogs such as hip dysplasia 28 and patellar luxation. 29 The absence of glenoid dysplasia shows that this is not the cause of MSI in our population, and hence, without note of other orthopaedic anatomical variations, suggests that an increase in soft tissue laxity is the likely explanation for the joint instability affecting these dogs. Whether or not this is due to an underlying hypermobility syndrome warrants further investigation.…”
Section: Discussionmentioning
confidence: 61%
“…These factors have the potential to cause instability independently, though the possibility of an interplay between the two exists, as seen with other polygenic, multifactorial traits in dogs such as hip dysplasia 28 and patellar luxation. 29 The absence of glenoid dysplasia shows that this is not the cause of MSI in our population, and hence, without note of other orthopaedic anatomical variations, suggests that an increase in soft tissue laxity is the likely explanation for the joint instability affecting these dogs. Whether or not this is due to an underlying hypermobility syndrome warrants further investigation.…”
Section: Discussionmentioning
confidence: 61%
“…9,17,19 Similarly, our retrospective data analysis did not support the role of sex as a risk factor for having cranial cruciate ligament rupture and patellar luxation, as already reported. 11,18,[20][21][22][23][24] Some authors found that female sex increased such risk 9,17,25 and others described more male dogs diagnosed with patellar luxation in their study populations. 6,20,25 Studies about the association between age and prevalence of cranial cruciate ligament rupture and patellar luxation have shown conflicting results.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, acquiring country-wise consistency in information may be required. For instance, breed-associated risks for developing canine lymphoma [37] and patellar luxation [38][39][40][41] differ among countries. Systematic genetic epidemiological research is possible, however it requires considerable efforts.…”
Section: Genetic Epidemiology Of Diseases In Each Breedmentioning
confidence: 99%